New Approaches to Telecom Receiver Design for Mitigating Radiation-Pollution in Environment: Solution towards Green Communications - Ahuja, Amit Kumar; Chakka, Ram (Current Approaches in Engineering Research and Technology Vol. 3, 2024)
Telecommunication technologies are expanding at a rapid pace and so is the EMF (Electromagnetic Field) radiation exposure from wireless devices and networks to living beings. Various research works carried out in the past have shown a positive correlation between EMF exposures and increased diseases among living beings, including humans. The intensity of the concern can be realized from the precautionary warning by the WHO (World Health Organization) regarding EMF exposure, especially for children and expecting women. This warrants the need for a solution that reduces EMF exposure without adversely affecting the Quality of Service (QoS), that is Bit-Error-Rate (BER). The work of this chapter is regarding an innovative solution developed by the authors, over many years, which has the potential to reduce the EMF exposure without affecting the QoS (BER). It is shown that the EMF exposure is applicable to a large class of correlated digital signals. Substantial improvements over the classical method are realized and demonstrated. Its impact on telecommunications performance measures is analysed.